Comparative analysis of MVD and RHZ in the treatment of primary glossopharyngeal neuralgia: A clinical report on 61 cases - Wang, Leibo; Liu, Qingjun; Dong, Xiaoxia; Wang, Junwei (Frontiers in Neurology, 2023)
Objective Clinical data on 61 patients (grouped by their treatment with MVD or RHZ) with glossopharyngeal neuralgia were analyzed retrospectively. A summary analysis of the effective rate and surgical complications of MVD and RHZ in the treatment of glossopharyngeal neuralgia was performed to observe the new surgical options for GN. Method From March 2013 to March 2020, 63 patients with GN were admitted to our hospital by the professional group of cranial nerve diseases. Two patients diagnosed with tongue and pharynx pain secondary to tongue cancer and upper esophageal cancer, respectively were excluded from the group. The remaining patients all met the diagnosis of GN, some of them were treated with MVD and others were treated with RHZ. The pain relief rate, long-term results, and complications of the patients in the two groups were well-organized and analyzed. Result Of the 61 patients, 39 were treated with MVD and 22 were treated with RHZ. In the early-stage patients (the first 23 patients), all of them were operated on with the MVD procedure except one patient without vascular compression. In the later-stage patients, MVD was performed for evident single arterial compression according to the intraoperative situation. And for compression of arteries with greater tension or PICA + VA complex compression, RHZ was performed. It was also performed in cases where vessels with tight adhesions to the arachnoid and nerves could not be easily separated, or where it was easy to damage the perforating arteries after separating the blood vessels, causing vasospasm, which affects the blood supply to the brainstem and cerebellum. RHZ was also performed if there was no clear vascular compression. The efficiency of both groups was 100%. In the MVD group, one case recurred 4 years after the initial operation, and RHZ was performed for reoperation. Complications related to the operation included one case of swallowing and coughing in the MVD group, and three cases in the RHZ group; two cases of uvula not centering in the MVD group, and five cases in the RHZ group. There was 2 patients in RHZ group lost taste in 2/3 of the backing of the tongue, though these symptoms mostly disappeared or decreased after follow-up. One patient in the RHZ group had developed tachycardia by the time of the long-term follow-up, but whether it was related to the surgery is still uncertain. In terms of serious complications, there were two cases of postoperative bleeding in the MVD group. Based on the clinical characteristics of the patients' bleeding, it was judged that the cause of the bleeding was ischemia and was related to an intraoperative injury to the penetrating artery of the PICA artery and vasospasm. Conclusion MVD and RHZ are effective methods for the treatment of primary glossopharyngeal neuralgia. MVD is recommended for cases where vascular compression is clear and easy to handle. However, for cases with complex vascular compression, tight vascular adhesions, difficult separation, and without clear vascular compression, RHZ could be performed. Its efficiency is equivalent to MVD, and there is no significant increase in complications such as cranial nerve disorders. There are few cranial nerve complications that seriously affect the quality of life of patients. RHZ helps to reduce the risk of ischemia and bleeding during surgery by reducing the risk of arterial spasms and injury to the penetrating arteries by separating the vessels due to separation of vessels during MVD. At the same time, it may reduce the postoperative recurrence rate.